A proposed homemaking education program for boys in the intermediate grades - Tanah, Sinal Mansurah Antong 1939- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1966)
The author proposed a Homemaking Education Program for boys in the elementary schools in Sulu. The study aims to give information and guidelines to teachers, supervisors, and curriculum planners in other divisions in planning similar programs in their respective schools. The study suggests a wide variety of learning activities that young boys can do and share with other members of the family. The program stresses the values of shared responsibilities in school, at home and in the community.
Thesis (Master of Arts in Teaching, major in Home Economics)--University of the Philippines Diliman; 1966
Keywords: Home economics -- Study and teaching